Answer:
<h2>a = 400/21, b = 580/21</h2>
Step-by-step explanation:
Small triangles are similar. Therefore, the sides are proportional
<em>cross multiply</em>
<em>divide both sides by 21</em>
![a=\dfrac{400}{21}](https://tex.z-dn.net/?f=a%3D%5Cdfrac%7B400%7D%7B21%7D)
For b, we can use the Pythagorean theorem:
![b^2=\left(\dfrac{400}{21}\right)^2+20^2\\\\b^2=\dfrac{160000}{441}+400\\\\b^2=\dfrac{160000}{441}+\dfrac{176400}{441}\\\\b^2=\dfrac{336400}{441}\to b=\sqrt{\dfrac{336400}{441}}\\\\b=\dfrac{\sqrt{336400}}{\sqrt{441}}\\\\b=\dfrac{580}{21}](https://tex.z-dn.net/?f=b%5E2%3D%5Cleft%28%5Cdfrac%7B400%7D%7B21%7D%5Cright%29%5E2%2B20%5E2%5C%5C%5C%5Cb%5E2%3D%5Cdfrac%7B160000%7D%7B441%7D%2B400%5C%5C%5C%5Cb%5E2%3D%5Cdfrac%7B160000%7D%7B441%7D%2B%5Cdfrac%7B176400%7D%7B441%7D%5C%5C%5C%5Cb%5E2%3D%5Cdfrac%7B336400%7D%7B441%7D%5Cto%20b%3D%5Csqrt%7B%5Cdfrac%7B336400%7D%7B441%7D%7D%5C%5C%5C%5Cb%3D%5Cdfrac%7B%5Csqrt%7B336400%7D%7D%7B%5Csqrt%7B441%7D%7D%5C%5C%5C%5Cb%3D%5Cdfrac%7B580%7D%7B21%7D)
The slope of the line given its equation is calculated through, m = -A / B. The slope of the given line is 4/3. The line perpendicular to it has the slope of -3/4. The slope-point form of the equation is,
y - y1 = m(x - x1)
where m is the slope and x1 and y1 the abscissa and ordinate of the point, respectively.
Substituting the values above,
y --2 = (-3/4)(x - 3)
Simplifying the equation gives 3x + 4y = 1.
Answer:
2
Step-by-step explanation:
![\frac{5^{2}-10 }{17-3*4} -1\\\frac{5^{2}-10 }{17-3*4} =3\\\=-3-1\\=2](https://tex.z-dn.net/?f=%5Cfrac%7B5%5E%7B2%7D-10%20%7D%7B17-3%2A4%7D%20-1%5C%5C%5Cfrac%7B5%5E%7B2%7D-10%20%7D%7B17-3%2A4%7D%20%3D3%5C%5C%5C%3D-3-1%5C%5C%3D2)
Answer:
option B
6
Step-by-step explanation:
Given in the diagram two triangles ABC and DEF,
length of the side AB = 2
length of the side DE = 12
Scale factor of triangle ABC to triangle DEF, is the scale factor of side AB to DE
AB : DE
2 : 12
1 : 12/2
1 : 6
this means triangle DEF is 6 times larger than triangle ABC
or
triangle ABC is 1/6 of triangle DEF
Answer:
Step-by-step explanation:
b = -4 - (8)*(0)
b = -4
y = 8x - 4